365 Things To Do With Paper And Cardboard - Fiona Watt (Bharat Usborne Publishing, 2011)
This is a fantastic collection of 365 fun, environmentally friendly activities using paper, card and all manner of materials to be found around the house. There's something to do for every day of the year, including a 3D cardboard city, sock monkeys, loo roll mice, foil birds, sweet wrapper bugs and many, many more. Every activity is clearly and vividly illustrated in an appealing and colourful style, with easy-to-follow step-by-step instructions.
Keywords: All About Arts -- All About Arts; Do It Yourself -- Do It Yourself